Four-month-old infant with intussusception presenting as altered mental status. (10th November 2014) - Maldonado, Luis; Takagishi, Jennifer
Objective: To remind pediatric care providers that an altered mental status can be the only presenting symptom for intussusception, a life-threatening diagnosis. Method: A case report that presents a unique presentation of intussusception: a 4-month old boy with neurological findings after a reported head injury. Conclusion: Diagnosis of intussusception in the pediatric population is highly dependent on its classical presenting signs and symptoms: sudden severe colicky abdominal pain, vomiting, and an abdominal mass in children between 3 months and 6 years of age. Consider that an altered mental status can be the only presenting symptom.